Clinical and pharmacological properties of incobotulinumtoxinA and its use in neurological disorders - Jost WH; Benecke R; Hauschke D; Jankovic J; Kaňovský P; Roggenkämper P; Simpson DM; Comella CL (Dove Medical Press, 2015)
Wolfgang H Jost,1 Reiner Benecke,2 Dieter Hauschke,3 Joseph Jankovic,4 Petr Kaňovský,5 Peter Roggenkämper,6 David M Simpson,7 Cynthia L Comella81Department of Neurology, University of Freiburg, Freiburg, Germany; 2Clinic and Policlinic for Neurology, University of Rostock, Rostock, Germany; 3Institute of Medical Biometry and Medical Informatics, University of Freiburg, Freiburg, Germany; 4Department of Neurology, Baylor College of Medicine, Houston, TX, USA; 5Department of Neurology, Palacky University Olomouc, Faculty of Medicine and Dentistry and University Hospital, Olomouc, Czech Republic; 6University Eye Clinic of Bonn, Bonn, Germany; 7Icahn School of Medicine at Mount Sinai, New York, NY, USA; 8Rush University Medical Center, Chicago, IL, USABackground: IncobotulinumtoxinA (Xeomin®) is a purified botulinum neurotoxin type A formulation, free from complexing proteins, with proven efficacy and good tolerability for the treatment of neurological conditions such as blepharospasm, cervical dystonia (CD), and post-stroke spasticity of the upper limb. This article provides a comprehensive overview of incobotulinumtoxinA based on randomized controlled trials and prospective clinical studies.Summary: IncobotulinumtoxinA provides clinical efficacy in treating blepharospasm, CD, and upper-limb post-stroke spasticity based on randomized, double-blind, placebo-controlled trials with open-label extension periods (total study duration up to 89 weeks). Adverse events were generally mild or moderate. The most frequent adverse events, probably related to the injections, included eyelid ptosis and dry eye in the treatment of blepharospasm, dysphagia, neck pain, and muscular weakness in patients with CD, and injection site pain and muscular weakness when used for treating spasticity. In blepharospasm and CD, incobotulinumtoxinA was investigated in clinical trials permitting flexible intertreatment intervals based on the individual patient’s clinical need; the safety profile of intervals shorter than 12 weeks was comparable to intervals of 12 weeks and longer. There were no cases of newly formed neutralizing antibodies during the Phase III and IV incobotulinumtoxinA trials. Phase III head-to-head trials of incobotulinumtoxinA versus onabotulinumtoxinA for the treatment of blepharospasm and CD have demonstrated therapeutic equivalence of both formulations. Additional Phase III trials of incobotulinumtoxinA in conditions such as lower-limb spasticity, spasticity in children with cerebral palsy, and sialorrhea in various neurological disorders are ongoing.Conclusion: IncobotulinumtoxinA is an effective, well-tolerated botulinum neurotoxin type A formulation. Data from randomized clinical trials and further observational studies are expected to help physicians to optimize treatment by tailoring the choice of formulation, dose, and treatment intervals to the patient’s clinical needs.Keywords: blepharospasm, botulinum toxin, cervical dystonia, incobotulinumtoxinA, spasticity, Xeomin